1999
DOI: 10.1034/j.1600-0420.1999.770411.x
|View full text |Cite
|
Sign up to set email alerts
|

Long-term survival after ruthenium plaque radiotherapy for uveal melanoma. A meta-analysis of studies including 1,066 patients

Abstract: ABSTRACT.Purpose: Most case series of patients managed by brachytherapy for uveal melanoma are small and survival data show considerable inter-study variation. The aim of this study was to summarise similarly structured case series by meta-analysis. Methods: A systematic review generated 5 similarly structured case series including survival data for 1,066 patients treated by ruthenium plaque radiotherapy for uveal melanoma. After assessing the inter-study clinical heterogeneity, data were weighed for study siz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
1
3

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(27 citation statements)
references
References 4 publications
2
21
1
3
Order By: Relevance
“…Furthermore, corneal pannus in dogs [10] is responsive to radiation therapy with 90 Sr, and long-term benefit can be achieved with minimal side effects. In radiotherapy of intraocular tumors, e.g., in the case of malign choroid melanomas, episcleral brachytherapy with 106 Ru ophthalmic plaques has proven to be successful [14,[16][17][18][19][20]. In a study [12], the authors reported that in the course of an internal clinical acceptance test of 106 Ru ophthalmic plaques, manufactured by the company Bebig, Berlin, Germany, the following shortcomings of industrial quality assurance, which are relevant to therapy, were discovered: risk of leakage as well as inconsistent dose rate specifications in the manufacturer's certificates, covering a range of 111%.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, corneal pannus in dogs [10] is responsive to radiation therapy with 90 Sr, and long-term benefit can be achieved with minimal side effects. In radiotherapy of intraocular tumors, e.g., in the case of malign choroid melanomas, episcleral brachytherapy with 106 Ru ophthalmic plaques has proven to be successful [14,[16][17][18][19][20]. In a study [12], the authors reported that in the course of an internal clinical acceptance test of 106 Ru ophthalmic plaques, manufactured by the company Bebig, Berlin, Germany, the following shortcomings of industrial quality assurance, which are relevant to therapy, were discovered: risk of leakage as well as inconsistent dose rate specifications in the manufacturer's certificates, covering a range of 111%.…”
Section: Introductionmentioning
confidence: 99%
“…The film color darkens during the first days after irradiation. At [25][26][27][28][29][30] o C are estimated to be no more than a few percent when a 24 hours post-irradiation time is used.…”
Section: Environmental Dependencementioning
confidence: 99%
“…A more limited application of beta sources is the treatment of choroidal melanoma [27] and retinoblastoma [28]. These malignant diseases are treated with concave ruthenium plaques that can be stitched to the eye.…”
Section: Melanoma Of the Eyementioning
confidence: 99%
“…7 Following the pioneering works of Moore 8 and Stallard 9 from the UK, advances in radiation physics have led to the development of lowenergy plaques such as ruthenium 106 plaque 10 which is predominantly used in Europe, and iodine 125 plaque 11 used in North America. Data derived from a large number of patients treated either with ruthenium 106 12 or iodine 125 plaque 11 have shown that plaque radiotherapy is effective in controlling the primary tumour, preserving the globe in the majority of treated patients, and preserving useful vision in up to half of the treated patients. However, plaque radiotherapy does not offer any survival advantage over enucleation.…”
mentioning
confidence: 99%